Screening for Hypertension and Diabetes Mellitus in Mothers of RT 04 RW 09 Vim Village, Abepura District - Hasmi, Hasmi; Makaba, Sarce (Jurnal Pengabdian Masyarakat Bestari, 2024)
This screening aims to detect people with Hypertension and Diabetes Mellitus in Residents of RT 09 RW 04 Vim Village, Abepura District. The method is to check blood pressure using digital tension and blood glucose test using Rapid Diagnostic Test. The results of the service found that the proportion of people who suffer from Hypertension is 73% > 40 years old, 62.3% of Non-Papuan tribes, 100% of civil servants and self-employed workers, and 63% of family history of Hypertension. The highest mothers with DM are >40 years old 18.9%, Papuan ethnicity 16.7%, private employment 22.2%, and there is a family history of DM as much as 15.8%. Respondents who had HT were 60%, and mothers who were DM 13.8%. Early detection is needed regularly, to prevent HT and DM diseases from complications with other diseases.